Cross section evaluation for a LWR pin lattices with thorium applications. (September 2017) - Velasquez, Carlos E.; Pereira, Claubia; Veloso, Maria Auxiliadora F.; Costa, Antonella L.
Highlights: Criticality calculations for KRITZ experiment was simulated for different ENDLs. The data cross sections were processed using the NJOY99.364 code. Four fuels based on thorium with 4% of fissile material were analysed for KRITZ. The results show the differences between different ENDL cross sections. Abstract: This work describes a cross section analysis using a KRITZ experiment modeled with the MCNP code for different ENDLs. The first goal is to validate the processing cross section at work temperature using the KRITZ benchmark for all the evaluated nuclear data libraries available, ENDF-VII.1, JEFF-3.1, JEFF-3.2, TENDL-2014, TENDL-2015, JENDL-4.0, RUSFOND and CENDL-3 at DEN/UFMG. The second goal is to use the same experiment (geometry, parameters, etc) at KRITZ benchmark and use it for thorium application. The new fuel based on thorium were spiked with different fissile nuclides such as 233 U, 235 U, 239 Pu and 241 Pu at 4% each fuel to increase the initial fission chain until it is self-sustained. The purpose is to compare the cross sections from the different ENDLs and find the most suitable ones. The results show that in the case of any application, the difference between ENDF/B, JEFF, JENDL and RUSFOND libraries are in a reliable interval.